Effects of Chemical Post-treatments on Structural and Physicochemical Properties of Silk Fibroin Films Obtained From Silk Fibrous Waste - Puerta, Melissa; Peresin, Maria S.; Restrepo-Osorio, Adriana (Frontiers in Bioengineering and Biotechnology, 2020)
Silk fibroin (SF) is a protein polymer claimed to have outstanding potential for medical applications. However, because of the manufacturing process, materials from regenerated SF exhibit a higher percentage of amorphous structures, causing the material to be water soluble, limiting its applications in wet biological environments. In order to increase the amount of crystalline structures and decrease the water solubility of SF materials, post treatment with alcohols is usually employed. SF can be obtained from silk fibrous wastes (SFW), usually discarded in silk textile processes. This represents an opportunity to produce materials with high added value from low-cost natural sources. In this study, SF was obtained from SFW and films were made thereof followed by a post treatment by immersion or in a saturated atmosphere of methanol (MeOH) or ethanol (EtOH), using different exposure times. The resulting films were analyzed according to crystallinity, percentage of crystalline and amorphous structures, and thermal stability. Also, water absorption and weight loss in aqueous media were determined. The results showed a significant increase in crystalline structures in all treated samples, varying according to the type and time of exposure to post treatment conducted, showing the highest increase in the case of the post treatment by immersion in MeOH for 1 h, with a 23 % increase over the untreated sample. This increase in crystallinity was reflected in an increase in the degradation temperature and a degradation rate of 5.3 % on day 7. The possibility of tuning the degree of crystallinity, as well as thermal stability and aqueous integrity of thin films of SFW, can be applied to adjust these materials to the requirements of specific biomedical applications.